Propuesta de implementación de un sitio web para la gestión de trámites administrativos, mediante gobierno electrónico en el Consejo Cantonal de Protección Integral de Derechos de Loja, año 2024. - Díaz Jiménez, Mathias Andrés (2024)
The purpose of the research is the proposal of a website for the management of administrative procedures through electronic government, this was identified through a situational diagnosis in the Cantonal Council of Integral Protection of Rights of Loja, detecting the lack of a digital means or mechanism, where the institution can generate a direct contact with users, this means orients the administrative plant of the Council to adopt a continuous improvement and thus a modernization within the public sphere. For this reason, this research proposal was proposed as an alternative solution to facilitate the simplification of procedures, access to information, participation and direct contact with citizens, allowing to provide users with a quality service. The methodology used was based on the use of the inductive method and an exploratory-descriptive scope, the theories used were Deming's PDCA continuous improvement cycle (1989), the theory of the diffusion of innovations and the theory of new public management, which are framed within the line of research of the GE, Likewise, the application of the information gathering instruments were (interview - focus group and observation sheet), which are framed within the aforementioned theories; likewise, relevant information for the elaboration of the research proposal was obtained through these instruments; Through this type of research it was possible to determine the use of the PESTEL and AMOFHIT tools, as well as the elaboration of a TOWS matrix based on the previous analysis carried out in the internal and external environment of the Council, in order to design strategies oriented to respond to the needs found in the institution.